(3eSfO GdaQOhSs - (3TjQhjg (B((3TjQhjI(B) (3Hf TgQOGQ Hf TjQh jg Hf afGNSQh, CHh TLGY GdOjdeqj GdgePGfj,J (B509 (3g` s
(3ChdgG (B:s
(3PcQ GdCMGOjK ai GdChGFd aVd efgG ai Chd eG Ndb Gddg YR hLd s
(3BNQgG (B:s
(3aUd ai EPG SejJe eMeOkG adGJLHghg hdG JMQehg hdGJbHMhg HhQc ai eMeO hHjJ ajg eMeO heLdS ajg eMeO hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJbYjHIs
(3UhQJ CLRGA ai ESJGfHhd ef ajV Gddg hdYd gPG ef CLRGA Jdc GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B183 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdMOjK h GdeUWdMs